Designing smart artifacts for adaptive mediation of social viscosity: Triadic actor-network enactments as a basis for interaction design (2012)
With the advent o f ubiquitous com puting, interaction design has broadened its object o f inquiry into how smart com putational artifacts inconspicuously act in people's everyday lives. A lthough user-centered design approaches rem ain useful for exploring how people cope w ith interactive systems, they cannot explain how this new breed of artifacts participates in people's sociality. U ser-centered design approaches assum e that humans control interactive systems, disregarding the agency o f smart artifacts